Effects of caffeine on central and peripheral fatigue during anaerobic exercise performance - A systematic review - Mesquita, R.; Kyröläinen, H.; Avela, J. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: It has been shown that caffeine ingestion delays fatigue and it seems to be ergogenic during high-intensity exercise. Caffeine may attenuate the loss of force-generating capacity induced by anaerobic exercise, but its mechanisms of action at the various levels of the motor pathway are not fully understood yet. The aim of this review was to systematically evaluate the existing literature about the effects of caffeine on central and peripheral fatigue during anaerobic exercise performance. Methods: Studies were identified by searching from the earliest record until February 2016 (week 1) using the MEDLINE (Ovid), PubMed and Web of Science. The search terms used were "caffeine" and "central fatigue" or "peripheral fatigue" or "muscle fatigue". Randomized controlled trials published in peerreviewed journals were considered for inclusion. Intake of caffeine and a measure of central and/or peripheral fatigue during anaerobic exercise were required in each study. Results and discussion: Nine studies with a total of 103 participants were included. Electromyographic (EMG) activity from 7 studies showed no effect of caffeine on muscle activation variables during submaximal isometric contractions and in anaerobic cycling exercise. Two of these studies also used intramuscular EMG and found no differences on firing rates between conditions. Only one study (Plaskett & Cafarelli, 2001) found a significantly higher EMG activity in the caffeine condition at the end of the protocol, possibly due to an improved motor unit synchronization. Effects of caffeine on the enhancement of calcium mobilization is still controversial. Fredholm et al (1999) showed that the doses required to achieve this effect would be toxic to humans. Nevertheless, one study showed an attenuated decrease of the twitch amplitude (Meyers & Cafarelli, 2005) and another one an offset of the decline in lowfrequency tetanic force (Tarnopolsky and Cupido, 2000) and, therefore, this hypothesis should not be dismissed. Caffeine`s effects on central excitability are clear, potentiating motor evoked potentials before task failure. This effect has been convincingly attributed to the mechanisms of adenosine receptor antagonism. However, it seems that this central effect is not associated with enhanced maximal voluntary activation (Kalmar and Cafarelli, 2004; Kalmar and Cafarelli, 2006), demonstrating that voluntary activation is not limited by central excitability.